Barriers of Implicative Language Between Laymen, Children, and Sophisticated Men - Nadia, Bibi (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2025)
This research examines the challenges encountered by rustic individuals in comprehending implicative language. Rustic individuals, characterized by their low levels of education and exposure to sophisticated linguistic nuances, face significant barriers when confronted with implicit communication. Residing in uncomplicated, culturally straightforward environments, these individuals are often unable to grasp the implicit meanings embedded within language, particularly in conversational contexts, which delves into the impediments posed by implicative language for individuals categorized as the